DIVERSITY OF MOLLUSCS (BIVALVES AND GASTROPODS) IN KABUNG ISLAND, WEST KALIMANTAN, INDONESIA - Warsidah; Apriansyah; Kushadiwijayanto, Arie Antasari; Helena, Shifa (Jurnal Ilmu Kelautan SPERMONDE, 2021)
Kabung Island is an island located in Bengkayang Regency, West Kalimantan, Indonesia. The characteristics of these waters are sandy, muddy and muddy sand. This type of water is compatible with the life of Gastropods and Bivalves. Both of them play an important role in an ecosystem because of their ability as a filter feeder that filters dissolved substances in the water, for a source of food for their survival. The abundance and diversity of molluscs are highly dependent on the conditions of the aquatic environment, such as substrate type, pH, turbidity, temperature, salinity and dissolved oxygen, availability of food, pollutants, predators and competitors. This study was aims to assess the diversity and abundance of molluscs on the Kabung island. The results on this research show that the highest diversity index is 1.94 which means that it is in moderate condition. The evenness index and dominance index values found to show a value of 0.88 which means high evenness so that a dominance value of 0.45 means that there are no molluscs that dominate on the Kabung island. Keywords: Abundance, Bivalves, Diversity, Gastropods, Mollusca.